SIPsmartER delivered through rural, local health districts: adoption and implementation outcomes - Kathleen J. Porter; Donna Jean Brock; Paul A. Estabrooks; Katelynn M. Perzynski; Erin R. Hecht; Pamela Ray; Natalie Kruzliakova; Eleanor S. Cantrell; Jamie M. Zoellner (BMC, 2019)
Abstract Background SIPsmartER is a 6-month evidenced-based, multi-component behavioral intervention that targets sugar-sweetened beverages among adults. It consists of three in-person group classes, one teach-back call, and 11 automated phone calls. Given SIPsmartER's previously demonstrated effectiveness, understanding its adoption, implementation, and potential for integration within a system that reaches health disparate communities is important to enhance its public health impact. During this pilot dissemination and implementation trial, SIPsmartER was delivered by trained staff from local health districts (delivery agents) in rural, Appalachian Virginia. SIPsmartER's execution was supported by consultee-centered implementation strategies. Methods In this mixed-methods process evaluation, adoption and implementation indicators of the program and its implementation strategy (e.g., fidelity, feasibility, appropriateness, acceptability) were measured using tracking logs, delivery agent surveys and interviews, and fidelity checklists. Quantitative data were analyzed with descriptive statistics. Qualitative data were inductively coded. Results Delivery agents implemented SIPsmartER to the expected number of cohorts (n = 12), recruited 89% of cohorts, and taught 86% of expected small group classes with > 90% fidelity. The planned implementation strategies were also executed with high fidelity. Delivery agents completing the two-day training, pre-lesson meetings, fidelity checklists, and post-lesson meetings at rates of 86, 75, 100, and 100%, respectively. Additionally, delivery agents completed 5% (n = 3 of 66) and 10% (n = 6 of 59) of teach-back and missed class calls, respectively. On survey items using 6-point scales, delivery agents reported, on average, higher feasibility, appropriateness, and acceptability related to delivering the group classes (range 4.3 to 5.6) than executing missed class and teach-back calls (range 2.6 to 4.6). They also, on average, found the implementation strategy activities to be helpful (range 4.9 to 6.0). Delivery agents identified strengths and weakness related to recruitment, lesson delivery, call completion, and the implementation strategy. Conclusions In-person classes and the consultee-centered implementation strategies were viewed as acceptable, appropriate, and feasible and were executed with high fidelity. However, implementation outcomes for teach-back and missed class calls and recruitment were not as strong. Findings will inform the future full-scale dissemination and implementation of SIPsmartER, as well as other evidence-based interventions, into rural health districts as a means to improve population health.